Country-level effects of the ECB's expanded asset purchase programme. Issue 2 (2nd July 2020) - Zlobins, Andrejs
ABSTRACT: This paper evaluates the macroeconomic effects of the European Central Bank's (ECB) Expanded asset purchase programme (APP) on Latvia and other euro area jurisdictions and investigates the cross-border transmission mechanism. To that end, we employ two different vector autoregressive (VAR) models, namely a bilateral structural VAR with block exogeneity (BSVAR-BE) and a multi-country mixed cross-section global VAR with stochastic volatility (MCS-BGVAR-SV). We find that the APP had a limited and weakly significant impact on Latvia's output while the effect on inflation has been robust due to depreciation of the euro. Regarding other jurisdictions, results suggest that the ECB's asset purchases had a larger impact on industrial production in the countries where it drove down long-term interest rates the most via portfolio rebalancing channel. Despite that, our evidence suggests that the APP was mainly transmitted to inflation via exchange rate depreciation rather than through aggregate demand-driven shifts in the Phillips curve.